Hispidulin Inhibits Mast Cell-Mediated Allergic Inflammation through Down-Regulation of Histamine Release and Inflammatory Cytokines - Kim, Dong Eun (Molecules, 2019)
Hispidulin (4′,5,7-trihydroxy-6-methoxyflavone) is a natural compound derived from traditional Chinese medicinal herbs, and it is known to have an anti-inflammatory effect. Here, we investigated the effect of hispidulin on the immunoglobulin E (IgE)-mediated allergic responses in rat basophilic leukemia (RBL)-2H3 mast cells. When RBL-2H3 cells were sensitized with anti-dinitrophenyl (anti-DNP) IgE and subsequently stimulated with DNP-human serum albumin (HSA), histamine and β-hexosaminidase were released from the cells by degranulation of activated mast cells. However, pretreatment with hispidulin before the stimulation of DNP-HSA markedly attenuated release of both in anti-DNP IgE-sensitized cells. Furthermore, we investigated whether hispidulin inhibits anti-DNP IgE and DNP-HSA-induced passive cutaneous anaphylaxis (PCA), as an animal model for Type I allergies. Hispidulin markedly decreased the PCA reaction and allergic edema of ears in mice. In addition, activated RBL-2H3 cells induced the expression of inflammatory cytokines (tumor necrosis factor-α and interleukin-4), which are critical for the pathogenesis of allergic disease, through the activation of c-Jun N-terminal kinase (JNK). Inhibition of JNK activation by hispidulin treatment reduced the induction of cytokine expression in the activated mast cells. Our results indicate that hispidulin might be a possible therapeutic candidate for allergic inflammatory diseases through the suppression of degranulation and inflammatory cytokines expression.